Bridging the policy gap: burnout among resident doctors and the urgent need for structured call hour regulations (Pyramid Journal of Medicine, 2026)
Burnout among resident doctors is a critical global concern, yet Nigeria lacks structured call-hour regulations. This study assessed the prevalence of burnout, its association with duty-hour practices, and explored contextual factors influencing residents’ well-being.A concurrent mixed-methods study was conducted among 300 residents in Kano tertiary hospitals, which included a self-administered survey on work-hour practices and the Maslach burnout inventory, and was analyzed using descriptive statistics and Chi-square tests using the Statistical Package for Social Sciences (SPSS) version 27; Focus Group Discussions (FGDs) and Key-Informant Interviews (KIIs) explored contextual factors.The mean age of participants was 32.50 (Standard Deviation, SD=4.85). Emotional exhaustion was reported by 89.3% of participants, depersonalisation by 48.3%, and low personal accomplishment by 47.7%. The overall prevalence of burnout was 63.7%. Burnout was directly proportional to call duration (p